The effects of active labour market policies for immigrants receiving social assistance in Denmark - Eskil Heinesen; Leif Husted; Michael Rosholm (Institute for the Study of Labor (IZA), 2011)
We estimate the effect of active labour market programmes on the exit rate to regular employment for non-western immigrants in Denmark who receive social assistance. We use the timing-of-events duration model and rich administrative data. We find large positive post-programme effects, and, surprisingly, even most in-programme effects are positive. The effects are largest for subsidized employment programmes, but effects are also large and significant for direct employment programmes and other programmes. The effects are larger if programmes begin after six months of unemployment. Implications of our estimates are illustrated by calculating effects on the duration to regular employment over a five-year period.
urn:nbn:de:101:1-201104134355
Keywords: J64; J24; J68; J61; C41; 330; programme evaluation; duration analysis; timing-of-events model; Arbeitsmarktpolitik; Migranten; Sozialhilfeempfänger; Wirkungsanalyse; Berufliche Integration; Statistische Bestandsanalyse; Dänemark